MiR-205 serves as a prognostic factor and suppresses proliferation and invasion by targeting insulin-like growth factor receptor 1 in human cervical cancer - Hui Pang; Xiuying Yue (Tumor Biology)
MicroRNAs are a kind of small and non-coding RNAs, which have been demonstrated to play an important role in the progression of human cervical cancer. Here, we found that the expression of miR-205 was low in cervical cancer cell lines and tissues, compared with matched non-tumor tissues and human endocervical epithelial cells. Also, miR-205 was inversely correlated with histological differentiation, metastasis, International Federation of Gynecology and Obstetrics stage, and the expression of insulin-like growth factor receptor 1 messenger RNA and protein. Besides, miR-205 or insulin-like growth factor receptor 1 expression is an independent prognostic factor. Mechanically, ectopic expression of miR-205 decreased proliferation, colony formation, and some proliferation/apoptosis-related proteins in cervical cancer cells. Ectopic expression of miR-205 caused G1 arrest. Luciferase reporter assays confirmed that binding of miR-205 to the 3′ untranslated region of insulin-like growth factor receptor 1 may potentially decrease the expression of insulin-like growth factor receptor 1. Notably, insulin-like growth factor receptor 1 overexpression attenuated the inhibitory effects of miR-205 on cell proliferation and invasion, while small interfering RNA–insulin-like growth factor receptor 1 enhanced the inhibitory effects of miR-205 on cell proliferation and invasion. In conclusion, our findings suggested that miR-205 serves as a prognostic factor and suppresses proliferation and invasion by targeting insulin-like growth factor receptor 1 in human cervical cancer. Thus, miR-205/insulin-like growth factor receptor 1 pathway may be of great benefit to cervical cancer patients.